A survey to determine the zone of equipoise for the Proximal FEmur Resection or Internal Fixation fOR Metastases (PERFORM) randomized controlled trial - Jessa Fogel; Vincent Y. Ng; Thomas Schubert; Jonathan Forsberg; R. Lor Randall; Ricardo Becker; Carol Morris; Michelle Ghert (Trials)
Abstract Objective The objective of this study was to establish a zone of clinical equipoise for the Proximal FEmur Resection or Internal Fixation fOR Metastases (PERFORM) randomized controlled trial, which will compare resection and endoprosthetic reconstruction to internal fixation for skeletal metastases of the proximal femur. Methods A survey was developed, piloted, and distributed to self-declared interested stakeholders in the PERFORM trial. The survey targeted orthopedic oncologists and was designed to assess patient and bone lesion characteristics that drive surgical decision-making in the treatment of skeletal metastases in the proximal femur. An Ethics Waiver was obtained at the lead academic institution and data was collected in the REDCap survey database. Results Responses were complete from 76 surgeons across North America, South America, Europe, Asia, and Africa. Response rate from self-declared interested stakeholders was 70%, with additional responses collected from a broader international audience. Responses indicate that a study population for which either resection and endoprosthetic reconstruction or internal fixation are acceptable options include (1) life expectancy at least 6 months, (2) bone loss of no more than 75% and no less than 25%, and (3) minimal to moderate risk for perioperative complications. Ninety-three percent of respondents indicated that they would be interested in participating in the PERFORM trial. Conclusion A preliminary zone of equipoise for the PERFORM trial includes patients with 25–75% bone loss, low to moderate risk of operative complications, and life expectancy of at least 6 months. Further stakeholder discussions have finalized the PERFORM trial protocol prior to study initiation.